Elevated Co2 and leaf longevity in the C[subscript 4] grassland-dominant Andropogon gerardii - Knapp, Alan K.; Bargmann, Naomi; Maragni, Laura A.; McAllister, Christine A.; Bremer, Dale J.; Ham, Jay M.; Owensby, Clenton E. (My University, 2009)
In central U.S. grasslands, plant and ecosystem responses to elevated CO2 are most pronounced when water availability is limited. In a northeast Kansas grassland, responses to elevated CO2 in leaf area, number, development, and longevity were quantified for the tallgrass prairie dominant, Andropogon gerardii. Plants were grown in open-top chambers (OTCs) modified to limit water availability and to maximize responses to elevated CO2. In OTCs with elevated (#2 ambient) levels of CO2, aboveground biomass production and leaf water potentials were increased significantly compared with those of plants in OTCs with ambient CO2. There were no differences in leaf area or leaf number per tiller in A. gerardii in elevated compared with ambient OTCs. However, leaf area in adjacent unchambered plots with greater water availability was significantly higher than in the OTCs. The time required for developing leaves to achieve maximum leaf area was reduced by 29%, and the period of time until leaves senesced was increased by 20% for plants exposed to elevated compared with ambient CO2. Thus, leaves of this C4 grass species expanded more rapidly (6 d) and remained green longer (9 d) when exposed to elevated CO2. Such CO2-mediated increases in leaf longevity in the dominant species may allow this grassland to respond more opportunistically to temporally variable rainfall patterns in high-CO2 environments. These responses should be included in leaf-based simulation models that attempt to mechanistically link physiological alterations to predicted canopy responses to increased CO2.
Keywords: Ecophysiology; Elevated carbon dioxide; Grassland; Leaf lifespan; Tallgrass prairie; Water relations